Effect of stocking density vis-à-vis dietary protein supply on growth performance, immune-competence and cost economics of growing turkey poults - ALI, IMTIYAJ; MAJUMDAR, S; MIR, NASIR AKBAR; MANDAL, A B; BHANJA, S K; GOEL, AKSHAT; MEHRA, MANISH (The Indian Journal of Animal Sciences, 2018)
A 10-week biological experiment was undertaken to evaluate the response of Beltsvilie Small White turkey poults to different floor space (0.6, 0.8, and 1.0 ft2/bird) and dietary protein levels (22%, 24% and 26% with similar dietary energy) in terms of growth performance, immune response, and serum biochemistry, following 3 × 3 factorial design. Each treatment was allocated 4 replicates out of which one replicate was maintained for the replacement of the dead birds, if any, to maintain the required stocking density. The body weight gain (BWG), feed intake (FI) and performance index (PI) of poults was significantly higher in 1.0 ft2 floor space during 0–4 weeks and 4–10 weeks of age. Similarly, higher BWG, FI, and PI were observed at 26% dietary protein level. The interaction effect between stocking density and protein levels during 0–4 week resulted in significantly higher FI at 0.8 ft2 floor space with 26% protein level and 1.0 ft2 floor space with 24% as well as 26% protein level. The feed conversion ratio (FCR), mortality pattern, immune response and immune organ weights of poults did not reveal any significant treatment effect. The feed cost/bird increased linearly with increasing floor space, and feed cost/kg weight gain and feed cost/ kg meat increased linearly with increasing protein levels. However, profit potential per meter square decreased linearly with decreasing stocking density. The study concluded that increasing the stocking density and decreasing the dietary protein level decrease the performance of poults, but the profit potential per meter square increases with increasing stocking density. Thus, the study recommends either the floor space of 0.8 ft2/bird with 26% dietary protein level or the floor space of 1.0 sq2/bird with 24% dietary protein level for growing turkey poults.